Globalization and the decline of social reform : into the twenty-first century - Teeple, Gary (Garamond Press, 2000)
Globalization is the coming of the 'triumph of capitalism, ' the growing ascendancy of economics over politics, of corporate demands over public policy, of private over public interest. It represents the approaching completion of the capitalization of the world, carried out by 'self-generating capital' in the form of transnational corporations within an increasingly coherent transnational regulatory regime. Neo-liberal policies at the national level, argues the author, represent the policy side of globalization, the political requirements of global capital, the harmonization of the national with the global. They mark the transition between two eras, from a world of national corporations and nation states to a world of transnational corporations and supranational regulatory agencies. The author examines the postwar conditions that gave rise to the modern welfare state and the politics of social democracy throughout the industrial world. He traces the transformation of these conditions in the 1970s with the coming of a computer-based mode of production and the consequent necessity for global relations of production. In the face of global assertions of the rights of corporate private property, he makes the case that the world's subordinate classes and peoples will have to create global means of resistance.